Food and Beverage Promotions in Minnesota Secondary Schools: Secular Changes, Correlates, and Associations With Adolescents' Dietary Behaviors. (December 2014) - Larson, Nicole; Davey, Cynthia S.; Coombes, Brandon; Caspi, Caitlin; Kubik, Martha Y.; Nanney, Marilyn S.
ABSTRACT BACKGROUND The purpose of this study was to describe promotions for unhealthy and healthy foods and beverages within Minnesota secondary schools from 2008 to 2012, and to examine associations with school‐level coordination of environmental improvements and students' dietary behaviors. METHODS The Minnesota School Health Profiles and Minnesota Student Survey data were used along with National Center for Education Statistics data to conduct analyses accounting for school‐level demographics. RESULTS There was no significant improvement over time in the proportion of schools that banned advertising for unhealthy products in school buildings, on school grounds, on buses, or in publications. Whereas more than two thirds of schools had implemented strategies focused on the promotion of fruits/vegetables by 2012, only 37% labeled healthful foods with appealing names and just 17% used price incentives to encourage healthy choices. The number of stakeholders representing different roles on school health councils was positively correlated with implementation of healthy food and beverage promotion strategies. Little evidence was found to support an influence of in‐school advertising bans or promotions on students' diets. CONCLUSIONS Policy changes are needed to protect students from food and beverage advertising and additional opportunities exist to reduce disparities in the selection of healthy options at school.